(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The study sought to explore the experiences of casual employees at a multinational company in Zimbabwe. An exploratory qualitative research approach was utilised in the study. Data from sixteen participants who had worked for the multinational company in Zimbabwe for at least six months were gathered using semi-structured interviews. The study found that most casual employees at the case multinational company in Zimbabwe have experienced their work negatively. The three main negative lived experiences that most of the research participants identified were job insecurity, income insecurity and occupational health and safety challenges. Only a few casual workers expressed that they experienced casual work positively and attributed this to work flexibility and the ability to acquire job related knowledge. The study’s findings made it clear that the lived experiences of casual employees at the case multinational company in Zimbabwe are largely negative. Hence, the current study recommends that the case multinational company in Zimbabwe should follow the provisions of the legal frameworks that govern labour casualisation in Zimbabwe in order to enhance the experiences of casual employees.